2022
DOI: 10.1186/s12903-022-02422-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of in vivo vertical root fracture using deep learning on cone-beam CT images

Abstract: Objectives Evaluating the diagnostic efficiency of deep learning models to diagnose vertical root fracture in vivo on cone-beam CT (CBCT) images. Materials and methods The CBCT images of 276 teeth (138 VRF teeth and 138 non-VRF teeth) were enrolled and analyzed retrospectively. The diagnostic results of these teeth were confirmed by two chief radiologists. There were two experimental groups: auto-selection group and manual selection group. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Deep learning has garnered considerable interest in medicine owing to its high learning capacity and demonstrated ability to automate intricate diagnostic and treatment planning tasks. In endodontics, deep learning has shown promise in detecting vertical root fracture [ 3 ] and special tooth anatomies like C-shaped canals [ 27 ], and taurodontism [ 28 ]. They may also assist in gauging treatment complexity to inform planning and referral needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep learning has garnered considerable interest in medicine owing to its high learning capacity and demonstrated ability to automate intricate diagnostic and treatment planning tasks. In endodontics, deep learning has shown promise in detecting vertical root fracture [ 3 ] and special tooth anatomies like C-shaped canals [ 27 ], and taurodontism [ 28 ]. They may also assist in gauging treatment complexity to inform planning and referral needs.…”
Section: Discussionmentioning
confidence: 99%
“…Root canal treatment involves cleaning, shaping and obturation of the root canal system to prevent or treat apical periodontitis [ 1 ]. Despite relatively high success rates (82–92%) [ 2 ], endodontic treatment still carries risks of failure that can be influenced by procedural errors and mishaps [ 3 ]. Studies have demonstrated that errors including apical perforation, failing to achieve patency due to ledges or blockages, and improper obturation length can significantly reduce success rates [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of image recognition, convolutional neural networks (CNNs) are usually ideal choices with existing methods having achieved over 80% Top-1 accuracy and over 95% Top-5 accuracy on ImageNet datasets [ 14 ], while also demonstrating excellent performance on medical image analysis [ 15 ]. Nowadays, the identification of objects in the image has been applied to a variety of aspects from daily photos to microscopic images [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…14 Previous studies have demonstrated that the performance of CNN models on caries and root fracture detections exhibited 80%-96% accuracy (equivalent to dentists/radiologists). 15,16 In implant dentistry, AI has been investigated for identifying anatomical landmarks 17 and dental implant brands 18 and predicting implant prognosis based on radiographic images. 19 While the condition of the edentulous ridge varies for each implant site, this study aimed to develop an AI model to automatically identify the deficiency of edentulous ridge from the cone-beam computed tomographic (CBCT) images and suggest adequate ridge classification.…”
Section: Introductionmentioning
confidence: 99%
“…Convolutional neural network (CNN), a category of deep learning (DL) AI algorithms, is particularly useful for image‐based learning as it can capture patterns and classify images without labeling manual characteristics 14 . Previous studies have demonstrated that the performance of CNN models on caries and root fracture detections exhibited 80%–96% accuracy (equivalent to dentists/radiologists) 15,16 . In implant dentistry, AI has been investigated for identifying anatomical landmarks 17 and dental implant brands 18 and predicting implant prognosis based on radiographic images 19 …”
Section: Introductionmentioning
confidence: 99%